The Emotional Intelligence and Burnout of In-service English Teachers in Yogyakarta - Azhra, Shabrina Yumna; Alsamiri, Yasir; Putro, Nur Hidayanto Pancoro Setyo (Jurnal Penelitian dan Evaluasi Pendidikan, 2023)
Emotional intelligence and burnout of teachers are highly discussed in previous studies. This study set out to examine (1) the dimensions of emotional intelligence, (2) the dimensions of burnout, (3) the level of burnout, and (4) the relationship among the dimensions of in-service English teachers in Yogyakarta. The method used in this study is a quantitative correlational study through a survey. The instruments used were questionnaires adapted from the Maslach Burnout Inventory (MBI) and The Schutte Self-Report Emotional Intelligence Test (SSEIT). The participants of this study were 204 in-service English teachers in Yogyakarta. The data were analyzed using Confirmatory Factor Analysis (CFA) to find out the dimensions of emotional intelligence and burnout of the teachers and Structural Equation Modelling (SEM) to find the relationship among the dimensions of EI and burnout. The findings show that the emotional intelligence emerged into four dimensions, namely perception of emotion, managing own emotion, managing other's emotions, and utilization of emotions, while the dimensions of teachers burnout emerged into four dimensions namely occupational exhaustion, depersonalisation, and personal accomplishment. Surprisingly the findings show something unusual, it contrasts with several previous findings regarding the level of teachers' burnout.